Use of Comparative Genomics To Resolve an Unusual Case of Aminoglycoside Susceptibility in the Melioidosis Pathogen Burkholderia pseudomallei in Bangladesh - Mirjam, Kaestl; Saika, Farook; Md. Shariful, Alam Jilani; Shaheda, Anwar; Tanvir, Ahmed Siddiqui; Mark, Mayo; Yuwana, Podin; Jessica R., Webb; David A., B. Dance; Bart J., Currie (The American Journal of Tropical Medicine and Hygiene, 2024)
Melioidosis is an emerging tropical infectious disease with a rising global burden caused by the environmental bacterium Burkholderia pseudomallei. It is endemic in Southeast and South Asia, including Bangladesh. A rare aminoglycosidesusceptible B. pseudomallei isolate (Y2019) has recently been reported from a melioidosis patient in Dhaka, Bangladesh. To understand the geographical origins of Y2019, we subjected it and 10 other isolates from Bangladesh to wholegenome sequencing. In a phylogenetic tree with a global set of B. pseudomallei genomes, most Bangladeshi genomes clustered tightly within the Asian clade. In contrast, Y2019 was closely related to ST881 isolates from Sarawak, Malaysian Borneo, a gentamicin-sensitive sequence type, suggesting infection in Borneo. Y2019 also contained the same gentamicin sensitivity conferring nonsynonymous mutation in the drug eux pump encoding the amrB gene. In the absence of a full travel history, whole-genome sequencing and bioinformatics tools have revealed the likely origin of this rare isolate.